The Giesel ejector: a practical appraisal of its ability to improve the performance of a steam locomotive - Davidson, Donald (Department of Mechanical Engineering, 2023)
An ejector (jet pump) is a continuous flow pump which utilises the kinetic energy in a high velocity fluid stream, to entrain end extract a second fluid from a given location.